Powdered composition, and composition
Patent Information
- Application Number
- JP2025058384
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0024】 本開示によれば、誘電正接を十分に低減することが可能な粉末組成物を提供することができる。また、誘電正接を十分に低減することが可能な組成物を提供することができる。
Abstract
Description
[Technical Field]
[0001] This disclosure relates to powder compositions and compositions. [Background technology]
[0002] Calcium titanate powder is known as a ceramic filler used in resins for electronic materials and the like. Such electronic material fillers require high dielectric constant and low dielectric loss tangent. Patent Document 1 describes an electronic material filler in which a predetermined amount of coupling agent is bonded to calcium titanate particles to adjust the carbon content. It is stated that such an electronic material filler can suppress the dielectric loss tangent while maintaining a high dielectric constant when mixed with a resin. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2022-156362 [Overview of the project] [Problems that the invention aims to solve]
[0004] This disclosure provides a powder composition capable of significantly reducing the dielectric loss tangent when mixed with a resin. It also provides a composition capable of significantly reducing the dielectric loss tangent. [Means for solving the problem]
[0005] One aspect of this disclosure provides the following powder compositions.
[0006] [1] A powder composition comprising a plurality of calcium titanate particles and a coupling agent that binds to the surface of the plurality of calcium titanate particles, wherein the carbon content is less than 0.1% by mass.
[0007] The powder composition described in [1] above has a coupling agent bonded to the surface of multiple calcium titanate particles, and its carbon content is less than 0.1% by mass. In such a powder composition, the carbon content derived from the coupling agent is sufficiently reduced even though the coupling agent is bonded. Therefore, the dielectric loss tangent when mixed with resin can be sufficiently reduced.
[0008] The powder composition described in [1] above may also be one of the following [2] to [7].
[0009] [2] The powder composition according to [1], comprising a silane coupling agent.
[0010] The powder composition described in [2] above contains a silane coupling agent, which allows for increased fluidity when the powder composition is mixed with a resin, while further reducing the dielectric loss tangent.
[0011] [3] The powder composition according to [2] wherein the silane coupling agent comprises at least one functional group selected from the group consisting of vinyl groups, amino groups, and epoxy groups.
[0012] The powder composition described in [3] above has functional groups suitable for silane coupling agents, and therefore, when the powder composition is mixed with a resin, it is possible to further reduce the dielectric loss tangent while increasing its fluidity.
[0013] [4] The powder composition according to any one of [1] to [3], wherein the overall average circularity of the plurality of calcium titanate particles is 0.90 or higher.
[0014] The powder composition described in [4] above has a high overall average circularity of multiple calcium titanate particles, which allows for increased fluidity when the powder composition is mixed with a resin, while further reducing the dielectric loss tangent.
[0015] [5] The powder composition according to any one of [1] to [4], wherein the average particle size of the plurality of calcium titanate particles measured by laser diffraction and scattering is 4 μm or more.
[0016] The calcium titanate powder described in the above [5] has a sufficiently large average particle diameter, and thus can further reduce the dielectric loss tangent while improving the fluidity when the powder composition is mixed with a resin.
[0017] [6] The powder composition according to any one of [1] to [5], which comprises a particle group having a particle diameter of 10 μm or more among the plurality of calcium titanate particles, wherein the average circularity of the particle group is 0.75 or more.
[0018] In the powder composition described in the above [6], the average circularity of the particle group having a particle diameter of 10 μm or more is 0.75 or more. Such a powder composition contains a large number of spherical particles in the particle group having a large particle diameter of 10 μm or more among the plurality of calcium titanate particles. Here, the calcium titanate particles having a particle diameter of 10 μm or more can be obtained by melting the raw material powder to coarsen the particles when producing the calcium titanate particles. Therefore, when the average circularity of the particle group having a particle diameter of 10 μm or more is 0.75 or more, it is considered that most of the calcium titanate particles obtained by melting are spherical. Such a powder composition can further reduce the dielectric loss tangent while improving the fluidity when the powder composition is mixed with a resin.
[0019] [7] The powder composition according to any one of [1] to [6], wherein when the carbon content of the powder composition before washing is defined as X0, and the carbon content of the powder composition after repeating a washing operation twice, in which a slurry liquid obtained by mixing 3 g of the powder composition and 37 g of acetone is centrifuged at 3500 rpm for 10 minutes and the acetone supernatant is discarded, is defined as X1, the carbon residual ratio calculated by X1 / X0×100 is 45% or more.
[0020] The powder composition described in [7] above has a sufficiently high carbon retention rate after washing. Because the coupling agent is firmly bonded to the surface of the calcium titanate particles, such a powder composition can further reduce the dielectric loss tangent while increasing the fluidity when the powder composition is mixed with the resin.
[0021] One aspect of this disclosure provides the following compositions.
[0022] [8] A composition comprising the powder composition described in any one of [1] to [7] above and a resin.
[0023] The composition described in [8] above includes the powder composition described in any one of [1] to [7] above. Therefore, the dielectric loss tangent can be sufficiently reduced. [Effects of the Invention]
[0024] According to this disclosure, it is possible to provide a powder composition capable of sufficiently reducing the dielectric loss tangent. Furthermore, it is possible to provide a composition capable of sufficiently reducing the dielectric loss tangent. [Brief explanation of the drawing]
[0025] [Figure 1] This figure shows an example of a thermal spraying facility for producing calcium titanate powder using the flame melting method. [Modes for carrying out the invention]
[0026] Embodiments of this disclosure are described below. However, the following embodiments are illustrative for the purpose of illustrating this disclosure and are not intended to limit this disclosure to the following. The upper or lower limits of numerical ranges explicitly stated in this disclosure may be replaced with any of the values shown in the examples. Furthermore, the upper and lower limits described individually may be combined in any way. The symbol "~" used in numerical ranges indicates a numerical range that includes the upper and lower limits. For example, "X~Y" indicates a numerical range of "X or greater and Y or less". Unless otherwise specified, the materials or components exemplified in this disclosure may be used individually or in combination of two or more.
[0027] <Powder composition> A powder composition according to one embodiment comprises a plurality of calcium titanate particles and a coupling agent that binds to the surface of the plurality of calcium titanate particles, and has a carbon content of less than 0.1% by mass. In this specification, "powder" means "an aggregate of a plurality of particles." The carbon contained in the powder composition may originate from the components of the coupling agent. Therefore, a powder composition with a carbon content within the above range can sufficiently bind the coupling agent to the surface of the calcium titanate particles and reduce the dielectric loss tangent when mixed with a resin.
[0028] The carbon content of the powder composition may be 0.070% by mass or less, 0.065% by mass or less, 0.050% by mass or less, 0.040% by mass or less, or 0.030% by mass or less. Such a powder composition can further reduce the dielectric loss tangent when mixed with the resin. The carbon content of the powder composition may be 0.005% by mass or more, or 0.010% by mass or more. Such a powder composition has the coupling agent sufficiently bonded to the surface of the calcium titanate particles and exhibits excellent fluidity when mixed with the resin.
[0029] The carbon content may be, for example, 0.005% by mass or more and less than 0.1% by mass, 0.005 to 0.070% by mass, 0.005 to 0.065% by mass, 0.005 to 0.050% by mass, 0.005 to 0.040% by mass, or 0.005 to 0.030% by mass. Such powder compositions exhibit an excellent balance of high fluidity and low dielectric loss tangent when mixed with resin. The carbon content can be measured by the method described in the examples. The carbon content can be measured, for example, using a carbon / sulfur simultaneous analyzer (LECO Corporation, product name "CS-444LS") and quantified using the calibration curve method. The carbon content may also be measured after the washing operation described later. That is, the carbon content may include both X0 and X1 described later.
[0030] Let X0 be the carbon content of the powder composition before washing. Let X1 be the carbon content of the powder composition after repeating a washing operation twice, in which 3 g of the powder composition and 37 g of acetone are mixed to obtain a slurry, centrifuged at 3500 rpm for 10 minutes, and the supernatant liquid of acetone is discarded. In this case, the residual carbon rate calculated as X1 / X0 × 100 may be 45% or more. Because the residual carbon rate is within the above range, the coupling agent is firmly bonded to the surface of the calcium titanate particles, thereby increasing the fluidity when the powder composition is mixed with the resin and further reducing the dielectric loss tangent.
[0031] From the viewpoint of further improving the fluidity when the powder composition is mixed with the resin, and further reducing the dielectric loss tangent, the carbon retention rate may be 50% or more, 60% or more, or 70% or more. The carbon retention rate may be 100% or less, or 98% or less. The range of the carbon retention rate may be, for example, 45-100%, 50-100%, 60-98%, or 70-98%.
[0032] The range of X0 may be, for example, 0.005% by mass or more and less than 0.1% by mass, 0.010 to 0.070% by mass, 0.010 to 0.065% by mass, or 0.015 to 0.060% by mass, and the range of X1 may be, for example, 0.010 to 0.080% by mass, 0.010 to 0.050% by mass, or 0.015 to 0.040% by mass. Powder compositions in which X0 and X1 are within the above ranges can further reduce the dielectric loss tangent while further increasing the fluidity when mixed with resin.
[0033] The coupling agent may include a silane coupling agent. By including a silane coupling agent, the coupling agent can firmly bond to the surface of the calcium titanate particles, thereby increasing the fluidity when the powder composition is mixed with the resin and further reducing the dielectric loss tangent.
[0034] The silane coupling agent may contain at least one functional group selected from the group consisting of vinyl groups, amino groups, and epoxy groups. In a powder composition using such a silane coupling agent, the coupling agent can bond more strongly to the surface of the calcium titanate particles because the silane coupling agent has a suitable functional group. Therefore, such a powder composition can further reduce the dielectric loss tangent while increasing the fluidity when mixed with the resin. The amino group may also include a phenylamino group.
[0035] Examples of silane coupling agents containing vinyl groups include "KBM-1003" (product name) manufactured by Shin-Etsu Chemical Co., Ltd. Examples of silane coupling agents containing amino groups include "KBM-573" (product name) manufactured by Shin-Etsu Chemical Co., Ltd. Examples of silane coupling agents containing epoxy groups include "KBM-403" (product name) manufactured by Shin-Etsu Chemical Co., Ltd.
[0036] In the powder composition, the overall average circularity of the calcium titanate particles may be 0.90 or higher, or 0.95 or higher. When the overall average circularity of the calcium titanate particles is within the above range, the proportion of nearly spherical particles in the powder composition increases, which improves the fluidity of the composition mixed with the resin and further reduces the dielectric loss tangent.
[0037] In a powder composition, the average circularity of the group of particles with a particle diameter of 10 μm or more may be 0.75 or higher. Such a powder composition contains many spherical particles among the larger particles of 10 μm or more, and can also be called spherical calcium titanate powder. A composition obtained by mixing such a powder composition with a resin has excellent fluidity without an increase in viscosity, and the dielectric loss tangent can be further reduced. From the viewpoint of further improving the fluidity of the above composition, the average circularity of the group of particles with a particle diameter of 10 μm or more among the group of calcium titanate particles may be 0.78 or higher, or 0.80 or higher.
[0038] The circularity of a powder composition can be measured using a powder image analysis device (for example, Sysmex Corporation's product name "FPIA-3000"). Specifically, the powder composition is dispersed in pure water to obtain a dispersion, and this dispersion is then flowed through a planar stretchable flow cell. The calcium titanate particles moving within the cell are recorded as an image using an objective lens. The equivalent circle diameter and projected perimeter of the calcium titanate particles are determined from the recorded image, and the circularity of the particles is calculated from the following equation (1). In the following equation (1), HD represents the equivalent circle diameter, and PM represents the projected perimeter of the particle. The equivalent circle diameter means the diameter of a perfect circle with the same area as the projected area of the particle. Circularity = π × HD / PM (1)
[0039] The overall average circularity of multiple calcium titanate particles in a powder composition can be determined by arithmetic mean of the circularity calculated for each image of the multiple calcium titanate particles contained in the powder composition using the procedure described above. The number of calcium titanate particles (number of circularity data points) used when calculating the overall average circularity of multiple calcium titanate particles may be 200 or more (for example, 200) from the viewpoint of ensuring sufficiently high measurement accuracy. The range of this number of calcium titanate particles may be, for example, 200 to 100,000.
[0040] The average circularity of a group of particles with a particle diameter of 10 μm or more can be determined by extracting images of particles with an equivalent circle diameter HD of 10 μm or more from the images of calcium titanate particles used to calculate the circularity described above. That is, the average circularity of a group of particles with a particle diameter of 10 μm or more can be determined by taking the arithmetic mean of the circularity calculated for each of the extracted images of calcium titanate particles with an equivalent circle diameter HD of 10 μm or more. The number of calcium titanate particles (number of circularity data points) used to determine this average circularity may be the same as when determining the overall average circularity of calcium titanate particles. When calculating the average circularity of a group of particles with a particle diameter of 10 μm or more, "particle diameter of 10 μm or more" means that the equivalent circle diameter HD is 10 μm or more.
[0041] When calculating the average circularity of a group of particles with a particle diameter of 10 μm or more, the number of particles with an equivalent circle diameter HD of 10 μm or more may be 100 or more, or 200 or more, from the viewpoint of ensuring sufficiently high measurement accuracy. The range of the number of images of particles with an equivalent circle diameter HD of 10 μm or more may be, for example, 100 to 1000.
[0042] In the powder composition, the volume fraction of particles with a particle diameter of 10 μm or more, as measured by laser diffraction / scattering, may be 25% or more, 26% or more, or 27% or more. The above particle group may be a group of calcium titanate particles. When the volume fraction of the group of calcium titanate particles with a particle diameter of 10 μm or more is within the above range, the proportion of nearly spherical particles in the calcium titanate particles contained in the powder composition increases, resulting in improved fluidity when mixed with resin and further reduction of dielectric loss tangent. The above volume fraction may be 40% or less, or 35% or less. The above volume fraction range may be, for example, 25-40% or 27-35%.
[0043] In the powder composition, the average particle size (D50) of multiple calcium titanate particles measured by laser diffraction / scattering may be 4 μm or more, 5 μm or more, or 6 μm or more. Powder compositions with D50 within the above range exhibit excellent fluidity when mixed with resin and can further reduce dielectric loss tangent. D50 may be 10 μm or less, or 9 μm or less. The range of D50 may be, for example, 4 to 10 μm, or 6 to 9 μm. D50 can be determined by calculating the particle size when the cumulative value from the smallest particle size reaches 50% of the total in the volume-based particle size distribution when the powder composition is measured by laser diffraction / scattering.
[0044] When the particle size D90 is defined as the particle size when the above cumulative value reaches 90% of the total, D90 may be 12-30 μm, 20-27 μm, or 22-25 μm. Powder compositions in which D90 is within the above range exhibit excellent fluidity when mixed with resin and can further reduce dielectric loss tangent.
[0045] When the cumulative value mentioned above reaches 10% of the total, the particle size D10 may be 1-5 μm, 2-4 μm, or 2-3 μm. Having D10 within these ranges allows for excellent fluidity when mixed with the resin and further reduces the dielectric loss tangent.
[0046] When the particle size at which the above cumulative value reaches 100% of the total is defined as D100, D100 may be 100 μm or less, or 90 μm or less. Powder compositions in which D100 is within the above range have even better fluidity when mixed with resin because D100 is not too large. D100 may be 80 μm or more. The range of D100 may be, for example, 80 to 100 μm, or 80 to 90 μm.
[0047] Laser diffraction and scattering methods can be used for measurement in accordance with the method described in JIS Z 8825:2013 "Particle size analysis - Laser diffraction and scattering methods". A laser diffraction particle size analyzer (manufactured by Microtrac Bell Co., Ltd., product name "MT3300EXII") can be used.
[0048] The BET specific surface area of the powder composition is 2.0 m². 2 / g or less, 1.5m 2 / g or less, or 1.2m 2 It may be less than / g. Powder compositions with a BET specific surface area within the above range are obtained by sufficient melting of the raw material particles. Therefore, the shape of each calcium titanate particle in the powder composition becomes closer to spherical. Such powder compositions have even better fluidity when mixed with resin. The BET specific surface area is 0.2m². 2 / g or more, or 0.5m 2 It may be greater than or equal to / g. The range of the BET specific surface area is, for example, 0.2 to 2.0 m². 2 / g, or 0.5~1.2m 2 The value may be / g. The BET specific surface area can be measured, for example, by the BET single-point method using nitrogen gas adsorption with a specific surface area measuring device (e.g., Mountec Co., Ltd., product name "MACSORB").
[0049] The relative permittivity of the powder composition may be 80 or less, 70 or less, or 60 or less. The relative permittivity of the powder composition may be 20 or more. The range of the relative permittivity of the powder composition may be, for example, 20 to 80, 20 to 70, or 20 to 60. The dielectric loss tangent of the powder composition may be 0.004 or less, or 0.003 or less. The dielectric loss tangent of the powder composition may be 0.001 or more. The range of the dielectric loss tangent of the powder composition may be 0.001 to 0.004, or 0.001 to 0.003. The insulating properties of the powder composition are improved when the relative permittivity and dielectric loss tangent are within the above ranges. The relative permittivity and dielectric loss tangent are determined by measuring a resin sheet containing the powder composition. Specifically, they can be determined by the method described in the examples.
[0050] When 22 parts by mass of a bisphenol F type epoxy resin having a kinematic viscosity of 40 mPa·s at 25°C is blended with 78 parts by mass of a powder composition, and the shear viscosities measured using a rheometer at a plate temperature of 30°C, 1 rpm, and 100 rpm are denoted as V1 and V100, respectively, the V100 / V1 ratio may be 0.1 to 0.7, 0.2 to 0.6, or 0.2 to 0.5. A composition containing a powder composition and resin having V100 / V1 within the above range has sufficient thixotropy and an excellent balance between shear viscosity at low shear rates and shear viscosity at high shear rates. Therefore, it has excellent workability.
[0051] V1 may be 300 Pa·s or less, 200 Pa·s or less, or 150 Pa·s. When such a powder composition is mixed with a resin to form a composition, the shear viscosity at a shear rate of 1 rpm is sufficiently low. Therefore, it has even better fluidity. V1 may be 20 Pa·s or more, or 40 Pa·s or more. The range of V1 may be, for example, 20 to 300 Pa·s, or 40 to 150 Pa·s.
[0052] V100 may be 1 to 100 Pa·s, 10 to 50 Pa·s, or 20 to 40 Pa·s. Compositions containing a powder composition and a resin in which V100 is within the above range exhibit even better fluidity and workability.
[0053] Examples of bisphenol F type epoxy resins include "Epicote 807" manufactured by Mitsubishi Chemical Corporation. Examples of rheometers include "Modular Compact Rheometer MCR 102" manufactured by Anton Paar. A conical cone (3 degrees) is used as the rotating rod of the rheometer.
[0054] The method for producing the powder composition in this disclosure is described below. The method for producing the powder composition comprises the steps of: spheroidizing a raw material powder containing calcium titanate powder by a powder melting method to obtain spherical calcium titanate powder; and mixing the spherical calcium titanate powder with a coupling agent to surface-treat the spherical calcium titanate powder.
[0055] The raw material powder may be amorphous calcium titanate powder. The raw material powder may have an average particle size (D50) of 1-30 μm, 2-10 μm, or 2-5 μm, from the viewpoint of the average particle size of the powder after spheroidization and the ease of handling or feeding the raw material powder. The average circularity of the raw material powder is not particularly limited. For example, "CT-3" (product name) manufactured by Kyoritsu Material Co., Ltd. can be used as the raw material powder.
[0056] The method for preparing the raw material powder is not particularly limited. For example, bulk powder of calcium titanate obtained by reacting titanium dioxide (TiO2) and calcium carbonate (CaCO3) under high-temperature conditions may be used as the raw material powder, or calcium titanate powder prepared by a wet process may be used as the raw material powder. From the viewpoint of ease of availability and cost reduction, calcium titanate powder prepared by a solid-phase process may be used as the raw material powder.
[0057] From the viewpoint of reducing dielectric loss tangent and ensuring the reliability of electronic materials, the raw material powder may contain impurities such as alkali metal elements like Li, Na, and K, metal elements like Fe, and anions like Cl and Br, with a content of 0.01% by mass or less.
[0058] A method for producing a powder composition includes a step of spheroidizing a raw material powder by a powder melting method to obtain spherical calcium titanate powder. The powder melting method is a method of heating the raw material powder to a high temperature condition equal to or higher than its melting point, and may be, for example, a method of performing spheroidization using a flame melting method in which the raw material powder is introduced into a flame to be melted. In the flame melting method, the average circularity of the calcium titanate powder can be improved by adjusting the thermal energy applied to the raw material powder.
[0059] As will be described later, the thermal energy applied to the raw material powder can be adjusted by, for example, adjusting the ratio between the flow rate of the supplied combustible gas and the supply amount of the raw material powder, the ratio between the flow rate of the supplied combustible gas and the flow rate of the combustion-supporting gas, and the like.
[0060] Flow rate of the supplied combustible gas (m 3 / h) and the supply amount of the raw material powder (kg / h) (combustible gas / raw material ratio: m 3 / kg) may be 0.2 (m 3 / kg) or more, or 0.5 (m 3 / kg) or more, from the viewpoint of applying sufficient thermal energy to the raw material powder to sufficiently melt the raw material powder. From the viewpoint of reducing thermal energy and suppressing re-melting of the obtained calcium titanate powder to improve the average circularity, the combustible gas / raw material ratio may be 5.0 (m 3 / kg) or less, or 4.0 (m 3 / kg) or less. The range of the combustible gas / raw material ratio may be, for example, 0.2 to 5.0 (m 3 / kg), or 0.5 to 4.0 (m 3 / kg).
[0061] The ratio of the flow rate of the supplied combustible gas to the flow rate of the auxiliary gas (combustible gas / auxiliary gas ratio) may be 0.05 or higher, or 0.07 or higher, from the viewpoint of sufficiently forming a flame to promote the melting of the raw material powder and improving the average circularity of the calcium titanate powder. The combustible gas / auxiliary gas ratio may be 0.25 or lower, or 0.20 or lower, from the viewpoint of suppressing the flame from becoming too large, preventing the calcium titanate powder from melting again and improving the average circularity. The range of the combustible gas / auxiliary gas ratio may be, for example, 0.05 to 0.25, or 0.07 to 0.20.
[0062] The combustible gas may be one or more mixed gases such as acetylene, propane, and butane. The mixed gas may be, for example, LPG. The auxiliary combustion gas may be an oxygen-containing gas. From the viewpoint of facilitating the combustion of the combustible gas, reducing the generation of conductive soot (carbon), and improving the insulating properties of the resulting calcium titanate powder, the oxygen-containing gas may be 99% by mass or more pure oxygen. From the viewpoint of reducing the calorific value of the gas, an inert gas such as air or argon may be mixed with the auxiliary combustion gas.
[0063] Figure 1 shows an example of a thermal spraying apparatus for producing calcium titanate powder by flame melting. The thermal spraying apparatus 100 is equipped with a burner 11 and a melting furnace 12. The burner 11 is connected to a combustible gas supply pipe 16, a combustion-supporting gas supply pipe 17, and a raw material supply pipe 18. The raw material powder, which is fed into the melting furnace 12 through the raw material supply pipe 18, is melted by the flame 19 generated from the burner 11. As a result, the raw material powders fuse together and their shape is adjusted, allowing spherical calcium titanate powder to be obtained. The obtained calcium titanate powder can be sucked up by a blower 15 and collected in a bag filter 14 through piping 13.
[0064] The melting furnace 12 is not limited to a vertical furnace body, but may also be a horizontal furnace or inclined furnace, which is horizontal in which the flame is blown out horizontally. The atmosphere inside the melting furnace 12 may be an environment with a high oxygen partial pressure from the viewpoint of suppressing the reduction of the raw material powder. The raw material powder supplied into the melting furnace 12 through the raw material supply pipe 18 may be supplied as powder, or it may be supplied in a slurry state in which the raw material powder is dispersed in water or alcohol.
[0065] The combustible gas may be supplied by the combustible gas supply pipe 16, and the auxiliary combustion gas may be supplied by the auxiliary combustion gas supply pipe 17. The flame 19 generated from the burner 11 may be formed using, for example, LPG as the combustible gas and oxygen as the auxiliary combustion gas. Note that the thermal spraying equipment is not limited to that shown in Figure 1.
[0066] The method for producing the powder composition includes a step of mixing the spherical calcium titanate powder obtained in the above step with a coupling agent and surface-treating the spherical calcium titanate powder. By surface-treating the calcium titanate powder with the coupling agent, a powder composition can be obtained in which the coupling agent is bonded to the surface of the calcium titanate powder. The powder composition obtained in this way has a reduced carbon content and can reduce the dielectric loss tangent when mixed with a resin. The coupling agent can be the same as that described in the above embodiment of the powder composition. For example, the coupling agent may include a silane coupling agent.
[0067] Surface Coverage Ratio (SCR) is a known indicator of how well a silane coupling agent is bonded to the surface of a material. The SCR can be adjusted by changing the amount of silane coupling agent added during the surface treatment process. SCR represents the ratio of the silane coupling agent's coverage area to the total surface area of the calcium titanate powder particles. For example, an SCR of 1.0 theoretically means that the surface of the calcium titanate particles is completely covered by a monolayer of the added silane coupling agent, and there is no excess silane coupling agent. SCR is the minimum coverage area (m²) specified by the silane coupling agent manufacturer. 2 It can be calculated based on the minimum coverage area (m²). The amount of coupling agent added (g) mixed with calcium titanate powder may be adjusted so that the SCR calculated based on the minimum coverage area becomes a desired value. For example, when surface treatment is performed so that the SCR is 1.0, the minimum coverage area (m²) of the silane coupling agent can be adjusted. 2 The amount of silane coupling agent added should be adjusted so that the product of (g) and the amount added (g) equals the total surface area of the calcium titanate powder particles. When surface treatment is performed so that the SCR is 0.25, the minimum coating area (m²) of the silane coupling agent should be adjusted. 2 The amount of silane coupling agent added should be adjusted so that the product of ( / g) and the amount added (g) equals 25% of the total surface area of the calcium titanate powder particles.
[0068] In the surface treatment process, a silane coupling agent may be added so that the SCR is 1.0 or less, 0.5 or less, or 0.4 or less. A powder composition prepared by blending a coupling agent so that the SCR is within the above range can further reduce the dielectric loss tangent while increasing the fluidity when mixed with the resin. A silane coupling agent may also be blended so that the SCR is 0.1 or more. The SCR range may be, for example, 0.1 to 1.0, 0.1 to 0.5, or 0.1 to 0.4. A powder composition prepared by blending a silane coupling agent so that the SCR is within the above range can further reduce the dielectric loss tangent while increasing the fluidity when mixed with the resin. Therefore, a composition obtained by mixing such a powder composition with a resin has an excellent balance between high fluidity and low dielectric loss tangent.
[0069] The coupling agent may be added to the calcium titanate powder using a dropper, sprayer, or sprayer. The calcium titanate powder and the coupling agent can be mixed using a ball mill, Henschel mixer, or vibrating fluid dryer. The mixing time may be 0.5 to 2 hours. The mixing temperature may be 70 to 110°C. By heating at the above temperature while mixing, drying can be performed simultaneously with mixing. In this way, a powder composition can be obtained. The endpoint of the surface treatment step may be when gases derived from the silyl group in the silane coupling agent (e.g., methanol and ethanol) are no longer detected.
[0070] The method for producing the powder composition may include, if necessary, other steps after the surface treatment step. Other steps include drying the obtained powder composition, crushing it, and classifying it. In the drying step, the heating temperature may be 120°C or lower. As the drying apparatus, for example, a hot air dryer can be used. The heating time may be 0.5 to 5 hours, or 1 to 3 hours. Drying may also be carried out by curing in a room temperature atmosphere.
[0071] The crushing step may be performed if the obtained powder composition is in the form of aggregates. The crushing step may be carried out by methods such as using an agate mortar and pestle, a ball mill, a vibratory mill, a jet mill, or a wet jet mill. Crushing may be carried out dry, or it may be carried out wet by mixing with a liquid such as water or alcohol. In wet crushing, the powder composition can be obtained by drying after crushing. Examples of drying methods include heat drying, vacuum drying, freeze drying, and supercritical carbon dioxide drying.
[0072] The classification process may be performed to obtain a powder composition having a desired average particle size (D50). Examples of classification methods include sieving, liquid cyclone, and air classification.
[0073] Furthermore, the method for producing the powder composition may include a washing step to reduce impurities in the powder composition.
[0074] <Composition> A composition according to one embodiment comprises the above-described powder composition and a resin. Because such a composition contains the above-described powder composition, the dielectric loss tangent can be reduced. The content of the powder composition in the composition may be 50 to 90% by mass, or 65 to 80% by mass, from the viewpoint of achieving both the fluidity and insulating properties of the resin.
[0075] The resin may include at least one resin selected from thermoplastic resins or thermosetting resins. Examples of resins include polyethylene resins, polypropylene resins, epoxy resins, silicone resins, phenolic resins, melamine resins, urea resins, unsaturated polyester resins, fluororesins, polyamide resins such as polyimide resins, polyamideimide resins, and polyetherimide resins, polyester resins such as polybutylene terephthalate resins and polyethylene terephthalate resins, polyphenylene sulfide resins, all aromatic polyester resins, polysulfone resins, liquid crystal polymer resins, polyethersulfone resins, polycarbonate resins, maleimide-modified resins, ABS resins, AAS (acrylonitrile-acrylic rubber-styrene) resins, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins, hydrocarbon elastomer resins, polyphenylene ether resins, aromatic polyene resins, etc. These may be used individually or in combination of two or more.
[0076] The composition may also contain a curing agent, a curing accelerator, a mold release agent, a coupling agent, a coloring agent, a flame retardant, and an ion scavenger, etc.
[0077] The composition can be manufactured by blending the above-mentioned powder composition and resin in a predetermined ratio and mixing them. Mixing equipment such as a sieve, a three-roll mill, a ball mill, and a planetary mixer can be used. These devices may be used in appropriate combinations.
[0078] Although several embodiments of this disclosure have been described above, this disclosure is not limited to the embodiments described above. For example, the powder composition may contain other trace components other than calcium titanate and the coupling agent. [Examples]
[0079] The contents of this disclosure will be explained in more detail below with reference to examples and comparative examples. However, this disclosure is not limited to the examples described below.
[0080] <Manufacturing of powdered compositions> (Comparative Example 1) Raw material powder (calcium titanate powder; manufactured by Kyoritsu Material Co., Ltd., product name "CT-3") was prepared. Using a thermal spraying apparatus as shown in Figure 1, the raw material powder was flame-melted using LPG as the combustible gas supplied from the combustible gas supply pipe 16 to the burner 11, and oxygen as the auxiliary gas supplied from the auxiliary gas supply pipe 17 to the burner 11, to obtain the calcium titanate powder of Comparative Example 1. Note that the flow rate of the supplied combustible gas was (m³ 3 The ratio of the supply rate of raw material powder (kg / h) to the amount of combustible gas (combustible gas / raw material) is 3.8 (m 3 ( / kg) and the flow rate of the combustible gas to be supplied and the flow rate of the auxiliary gas (m 3 The ratio (combustible gas / combustible gas ratio) to / h was set to 0.09.
[0081] (Example 1) 300 g of calcium titanate powder and 800 g of 10 mm diameter alumina balls were placed in a 1 L polyethylene container. A silane coupling agent containing vinyl groups, "KBM-1003" (product name, manufactured by Shin-Etsu Chemical Co., Ltd., minimum coverage area: 526 m²), was added to this polyethylene container using a dropper. 2 A silane coupling agent was added ( / g). At this time, the silane coupling agent was added so that the calculated value (SCR), which represents the ratio of the coating area of the silane coupling agent to the total surface area of the calcium titanate powder particles, was 0.13. This polyethylene container was attached to a ball mill, and the ball mill was rotated at 70 rpm for 1 hour while being struck with a knocker to mix the calcium titanate powder and the silane coupling agent. This performed surface treatment on the calcium titanate powder. After that, the obtained powder was taken out and dried with hot air at 100°C for 1 hour, and then sieved using a sieve with a mesh size of 106 μm, and the powder below the sieve was collected to obtain the powder composition of Example 1. The yield of the powder composition below the sieve, based on the powder before sieving, was 98% by mass or more.
[0082] (Examples 2-5) The powder composition was obtained using the same procedure as in Example 1, except that the amount of silane coupling agent added was changed so that the SCR was the value shown in Table 1.
[0083] (Example 6) The silane coupling agent used is "KBM-573" (product name, manufactured by Shin-Etsu Chemical Co., Ltd., minimum coverage area: 305 m²), a silane coupling agent containing an amino group. 2 A powder composition was obtained using the same procedure as in Example 1, except that the value was changed to ( / g).
[0084] (Examples 7-9, Comparative Example 2) The powder composition was obtained using the same procedure as in Example 6, except that the amount of silane coupling agent added was changed so that the SCR value was as shown in Table 2.
[0085] (Example 10) The silane coupling agent is "KBM-403" (product name, manufactured by Shin-Etsu Chemical Co., Ltd., minimum coverage area: 330m²), which contains an epoxy group. 2 A powder composition was obtained using the same procedure as in Example 1, except that the value was changed to ( / g).
[0086] (Examples 11, 12, Comparative Example 3) The powder composition was obtained using the same procedure as in Example 10, except that the amount of silane coupling agent added was changed so that the SCR was the value shown in Table 3.
[0087] <Evaluation of powdered compositions> The carbon content, average circularity, particle size distribution, BET specific surface area, and shear viscosity when mixed with resin were measured for the calcium titanate powder of Comparative Example 1, and for each powder composition of each example and Comparative Examples 2 and 3 (hereinafter referred to as "each measurement sample"). In addition, the dielectric constant and dielectric loss tangent of each measurement sample were measured according to the following procedure.
[0088] [Measurement of carbon content] The carbon content of each sample was measured as the mass %) of 0.3 g of each sample using a carbon / sulfur simultaneous analyzer (LECO, product name "CS-444LS"). Quantitative analysis was performed using the calibration curve method. The results are shown in Tables 1-3.
[0089] The carbon content of each sample after washing was determined by the following procedure. 3 g of each sample was added to 37 g of acetone and stirred for 30 minutes to obtain a slurry. Centrifugation was performed at 3500 rpm for 10 minutes using a centrifuge to separate each sample from the acetone, and the supernatant (acetone) was discarded. This washing operation with acetone was repeated a total of two times, and each washed sample was dried at 120°C for 2 hours. The carbon content (mass%) in 0.3 g of each washed sample was measured using a carbon / sulfur simultaneous analyzer (LECO, product name "CS-444LS") and quantified using the calibration curve method. The carbon content of each sample before washing was taken as X0, and the carbon content of each sample after washing was taken as X1. The remaining carbon percentage (%) was calculated by calculating X1 / X0 × 100. The results are shown in Tables 1-3.
[0090] [Measurement of average circularity] The average circularity of each sample was measured using a powder image analyzer (Sysmex Corporation, product name "FPIA-3000") following the procedure below. After dispersing each sample in pure water to obtain a dispersion, this dispersion was flowed into a planar stretchable flow cell, and the calcium titanate particles moving within the cell were recorded as images using an objective lens. The equivalent circle diameter and projected perimeter of the calcium titanate particles were determined from the recorded images, and the circularity of the particles was calculated from the following equation (1). In the following equation (1), HD represents the equivalent circle diameter, and PM represents the projected perimeter of the particle. The circularity of 200 arbitrary particles was calculated from the particle images obtained from the entire recorded sample, and this was used as the overall average circularity of the calcium titanate particles. The results are shown in the "Average Circularity" column of Tables 1 to 3. Circularity = π × HD / PM (1)
[0091] Furthermore, from the particle images of the entire sample described above, images of particles with an equivalent circle diameter (HD) of 10 μm or more were extracted. The number of extracted particles with an equivalent circle diameter (HD) of 10 μm or more was 100 or more. The circularity was calculated for each image of the extracted particles with an equivalent circle diameter (HD) of 10 μm or more, and the average circularity of multiple calcium titanate particles with a particle diameter of 10 μm or more was calculated. The results are shown in the "Average Circularity of Particles with a Diameter of 10 μm or More" column in Tables 1 to 3.
[0092] [Particle size distribution measurement] The particle size distribution of each sample was measured using a laser diffraction particle size analyzer (Microtrac Bell Co., Ltd., product name "MT3300EXII"). The sample was measured in a glass beaker at a depth of 80 cm². 3 Pure water and 0.1 g of each sample were added and dispersed for 1 minute using an ultrasonic homogenizer (Sonics & Materials, product name "Vibra Cell", model number VC505). The dispersed solution of each sample was added drop by drop using a dropper to a laser diffraction particle size distribution analyzer, and measurements were taken 30 seconds after the predetermined amount was added. The particle size distribution was calculated from the light intensity distribution data of the diffraction / scattered light of each sample detected by the sensor in the laser diffraction particle size distribution analyzer.
[0093] In the obtained particle size distribution, the particle size at which the cumulative value from smallest particle size reached 10% of the total was defined as D10, the particle size at which the cumulative value reached 50% was defined as D50, the particle size at which the cumulative value reached 90% was defined as D90, and the particle size at which the cumulative value reached 100% was defined as D100. D10, D50, D90, and D100 were calculated separately. In addition, the volume fraction of the particle group with a particle size of 10 μm or larger was calculated. The results are shown in Tables 1 to 3.
[0094] [BET specific surface area measurement] The BET specific surface area of each sample was determined using a specific surface area analyzer (Mountec Co., Ltd., product name "MACSORB") by the single-point BET method with nitrogen gas adsorption. Nitrogen gas was used as the adsorption gas, and helium gas was used as the carrier gas. Measurements were performed after drying and degassing 1.1 to 1.4 g of each sample at 300°C for 30 minutes. The results are shown in Tables 1 to 3.
[0095] [Shear viscosity measurement] An evaluation resin composition was obtained by mixing each measurement sample with a liquid bisphenol F type epoxy resin (manufactured by Mitsubishi Chemical Corporation, trade name "Epicoat 807") having a kinematic viscosity of 40 mPa·s at 25°C, so that each measurement sample was present in a concentration of 78% by mass. The evaluation resin composition was measured using a rheometer (manufactured by Anton Paar, trade name "Modular Compact Rheometer MCR 102") equipped with a conical cone (3 degrees) at a measurement temperature of 30°C, measuring the shear viscosity V1 (Pa·s) at a shear rate of 1 (1 / s) and the shear viscosity V100 (Pa·s) at a shear rate of 100 (1 / s). The ratio V100 / V1 was calculated using the measured viscosities. The results are shown in Tables 1-3.
[0096] [Measurement of dielectric properties (relative permittivity and dielectric loss tangent)] The dielectric properties of each sample were measured using a powder dielectric constant analyzer (manufactured by Keycom Co., Ltd., product name "TM Cavity Resonator" (cylindrical cavity resonance method)). PTFE resin cell (cylindrical, volume 1154 cm³) 3 After filling each sample container with 2.5 to 3.0 g of each sample and setting it in the apparatus, the resonance peak at 1 GHz was read, and the relative permittivity and dielectric loss tangent were measured. The results are shown in Tables 1 to 3.
[0097] [Table 1]
[0098] [Table 2]
[0099] [Table 3]
[0100] As shown in Tables 1-3, the powder compositions of Examples 1-12, which contain multiple calcium titanate particles and a coupling agent that binds to their surfaces, and have a carbon content of less than 0.1% by mass, were confirmed to be able to sufficiently reduce the dielectric loss tangent. [Industrial applicability]
[0101] According to this disclosure, it is possible to provide a powder composition capable of sufficiently reducing the dielectric loss tangent. Furthermore, it is possible to provide a composition capable of sufficiently reducing the dielectric loss tangent. [Explanation of Symbols]
[0102] 100... Thermal spraying equipment, 11... Burner, 12... Melting furnace, 13... Piping, 14... Bag filter, 15... Blower, 16... Combustible gas supply pipe, 17... Combustible gas supply pipe, 18... Raw material supply pipe, 19... Flame.
Claims
1. A powder composition comprising a plurality of calcium titanate particles and a coupling agent that binds to the surface of the plurality of calcium titanate particles, wherein the carbon content is less than 0.1% by mass.
2. The powder composition according to claim 1, wherein the coupling agent comprises a silane coupling agent.
3. The powder composition according to claim 2, wherein the silane coupling agent comprises at least one functional group selected from the group consisting of vinyl groups, amino groups, and epoxy groups.
4. The powder composition according to any one of claims 1 to 3, wherein the overall average circularity of the plurality of calcium titanate particles is 0.90 or higher.
5. The powder composition according to any one of claims 1 to 3, wherein the average particle size of the plurality of calcium titanate particles measured by laser diffraction / scattering is 4 μm or more.
6. The powder composition according to any one of claims 1 to 3, wherein the plurality of calcium titanate particles include a group of particles having a particle diameter of 10 μm or more, and the average circularity of the group of particles is 0.75 or more.
7. The powder composition according to any one of claims 1 to 3, wherein the carbon content of the powder composition before washing is X0, and the slurry obtained by mixing 3 g of the powder composition and 37 g of acetone is centrifuged at 3500 rpm for 10 minutes, and the washing operation of discarding the supernatant liquid of the acetone is repeated twice, and the carbon content of the powder composition after this operation is X1, the remaining carbon rate calculated by X1 / X0 × 100 is 45% or more.
8. A composition comprising the powder composition according to any one of claims 1 to 3 and a resin.
Citation Information
Patent Citations
Filler for electronic materials, method for producing filler for electronic materials, and resin composition containing filler for electronic materials, and slurry for electronic materials
JP2022156362A